2023
DOI: 10.3390/ijms241713342
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Nanozyme-Mediated Strategies for Pathogen Detection and Control

Tianyi Ma,
Kunlun Huang,
Nan Cheng

Abstract: Pathogen detection and control have long presented formidable challenges in the domains of medicine and public health. This review paper underscores the potential of nanozymes as emerging bio-mimetic enzymes that hold promise in effectively tackling these challenges. The key features and advantages of nanozymes are introduced, encompassing their comparable catalytic activity to natural enzymes, enhanced stability and reliability, cost effectiveness, and straightforward preparation methods. Subsequently, the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 213 publications
0
1
0
Order By: Relevance
“…Nanoenzymes are diverse but most of them mediate catalytic reactions (mainly redox reactions) [205]. The redox-catalyzed activity of nanoenzymes generates a free radical storm that breaks the ROS balance, thus destroying the integrity of cell membranes, degrading a wide range of molecules, including nucleic acids, proteins, polysaccharides, and lipids, and destroying the morphology of bacteria, thereby killing MDR bacteria [206][207][208][209]. Yao et al [210] reported the use of pathogen-targeting bimetallic BiPt nanozymes exhibiting dual-enzymatic activities, including peroxidase-mimic and oxidase-mimic activities, for the nanocatalytic treatment of an MDR pathogen.…”
Section: Combination Antibiotics and Phagesmentioning
confidence: 99%
“…Nanoenzymes are diverse but most of them mediate catalytic reactions (mainly redox reactions) [205]. The redox-catalyzed activity of nanoenzymes generates a free radical storm that breaks the ROS balance, thus destroying the integrity of cell membranes, degrading a wide range of molecules, including nucleic acids, proteins, polysaccharides, and lipids, and destroying the morphology of bacteria, thereby killing MDR bacteria [206][207][208][209]. Yao et al [210] reported the use of pathogen-targeting bimetallic BiPt nanozymes exhibiting dual-enzymatic activities, including peroxidase-mimic and oxidase-mimic activities, for the nanocatalytic treatment of an MDR pathogen.…”
Section: Combination Antibiotics and Phagesmentioning
confidence: 99%
“…Bacterial infections pose a significant threat to human health, presenting a substantial global challenge that endangers public well-being and places a substantial economic burden on society. During the twentieth century and the early years of the twenty-first century, antibiotics were the primary choice for treating infectious diseases, serving as the foundation of modern medicine’s approach to combatting bacterial infections. , However, the irresponsible utilization and administration of antibiotics have caused the antibiotic tolerance and resistance , and highlighted the importance of researching alternative therapeutic techniques. Such efforts are focused not only on combating more efficiently bacterial infections but also on reducing the chance of developing antimicrobial resistance .…”
Section: Introductionmentioning
confidence: 99%